Twenty questions from the surgeon to the radiologist to better plan an open partial horizontal laryngectomy - Crosetti, Erika; Succo, Giovanni; Sapino, Silvia; Bertotto, Ilaria; Cirillo, Stefano; Petracchini, Massimo; Fondello, Gabriele; Arrigoni, Giulia; Tascone, Martina; Piazza, Cesare; Farina, Davide; Ravanelli, Marco (Frontiers in Oncology, 2024)
Open partial horizontal laryngectomies (OPHLs) represent a valuable therapeutic option for tumours of intermediate T-category and, in very selected cases, for locally advanced tumours with low-volume extra-laryngeal extension. The eligibility of cases treatable with this type of surgery has been increased by the introduction of the modular approach in OPHL planning. This strategy follows the introduction of the classification proposed by the European Laryngological Society based on the extent of the horizontal resection. Optimization of the selection is the result of a meticulous workup process involving close cooperation between experienced surgeons and radiologists, followed by the final quality control of pathologists. Computed tomography and magnetic resonance imaging are study methods whose pearls and pitfalls are well known, especially when performed at a high level of expertise. In this paper, based on the experience of two high-volume centres, a checklist of 20 questions addressed by the surgeon to the radiologist before planning an OPHL is proposed. Considerations about the case-selection are reported for each of the questioned parameters. A very simple question and answer process is easy to understand and mainly addressed to the less experienced colleagues who wish to increase their knowledge and skills in performing this type of surgery.Erika Crosetti, study conception and design, drafting the article, final approval of the version to be published; Giovanni Succo, study conception and design, drafting the article, final approval of the version to be published; Stefano Cirillo and Massimo Petracchini, selection of the radiologic findings; Gabriele Fondello and Ilaria Bertotto, selection and review of the radiologic findings, drafting the article; Silvia Sapino, data collection, drafting the article; Giulia Arrigoni e Martina Tascone, data collection; Davide Farina and Cesare Piazza, final approval of the version to be published; Marco Ravanelli, study conception and design, selection and review of the radiologic findings, drafting the article, final approval of the version to be published.